2015
DOI: 10.1016/j.jconhyd.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal dynamics of organohalide-respiring bacteria in a heterogeneous PCE–DNAPL source zone

Abstract: Effective treatment of sites contaminated with dense non-aqueous phase liquids (DNAPLs) requires detailed understanding of the microbial community responses to changes in source zone strength and architecture. Changes in the spatial and temporal distributions of the organohalide-respiring Dehalococcoides mccartyi (Dhc) strains and Geobacter lovleyi strain SZ (GeoSZ) were examined in a heterogeneous tetrachloroethene- (PCE-) DNAPL source zone within a two-dimensional laboratory-scale aquifer flow cell. As part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 75 publications
1
7
0
Order By: Relevance
“…Results indicate that, within 7 weeks following bioaugmentation and biological amendment delivery, PCE concentrations showed a substantial (~90%) decrease, with an approximate stoichiometric increase in DCE (although the DCE concentrations in 37‐B11s at 46 days following bioaugmentation appear anomalously low). These results are consistent with previous studies that show DCE as the primary dechlorination daughter product when PCE DNAPL is present (Haest et al ; Schaefer et al ; Cápiro et al ). The increases in chloride concentrations, particularly between 130 and 205 days, also confirm reductive dechlorination is occurring (Figure ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Results indicate that, within 7 weeks following bioaugmentation and biological amendment delivery, PCE concentrations showed a substantial (~90%) decrease, with an approximate stoichiometric increase in DCE (although the DCE concentrations in 37‐B11s at 46 days following bioaugmentation appear anomalously low). These results are consistent with previous studies that show DCE as the primary dechlorination daughter product when PCE DNAPL is present (Haest et al ; Schaefer et al ; Cápiro et al ). The increases in chloride concentrations, particularly between 130 and 205 days, also confirm reductive dechlorination is occurring (Figure ).…”
Section: Resultssupporting
confidence: 93%
“…Bioaugmentation has been shown to enhance the rate of PCE dense nonaqueous phase liquid (DNAPL) dissolution in sand columns and flow cells by factors ranging from approximately 1.1 to 21 (Glover et al ; Amos et al ; Amos et al ). Cápiro et al () recently showed in a laboratory study that the dissolution enhancement factor is related to the DNAPL architecture in unconsolidated materials (i.e., pools vs. ganglia). However, batch and column studies have indicated that the presence of PCE as a DNAPL can have an inhibitory effect on the reductive dechlorination of PCE during bioaugmentation (Adamson et al ).…”
Section: Introductionmentioning
confidence: 99%
“…A ratio of vcrA -to-16S copies that is greater than 1 is unexpected given what is known about Dehalococcoides and could mean that there are multiple copies of the vcrA gene in the genome or that vcrA is found in another organism or replicated separately from the genome, perhaps in a phage. Although this anomalous result is most likely due to PCR measurement error, others have also found high numbers of copies of vcrA relative to Dhc 16S rRNA in some field samples. , Our results may indicate that the vcrA gene can be mobilized, and this mobilization event is triggered by the stress of the high concentrations of nZVI–CMC that temporarily existed near this well. Further studies will be required to test this hypothesis.…”
Section: Resultsmentioning
confidence: 55%
“…Acetylene is not a known biotic reductive dechlorination product of TCE, and therefore serves as an indicator of abiotic dechlorination. While ethene can be both a biotic and abiotic TCE dechlorination product, the absence of measurable VC and DCE accumulation suggests that the ethene is likely an abiotic transformation product. , For sediments 1 through 3, results show that the abiotic generation of the TCE dechlorination products was occurring throughout the duration of the experiment, as evidenced by the increasing trends in acetylene and ethene. However, as noted in the Figure S1 caption, the lack of a replicate for the sediment 3 acetylene data at 106 days warrants interpreting this final data point with caution.…”
Section: Resultsmentioning
confidence: 88%